UNVEILING THE DIVERSE LANGUAGE LEARNING STRATEGY OF INDONESIAN EFL TWINS: A CASE STUDY - Benni Ichsanda Rahman Hz; Rita Seroja Br Ginting (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
Each individual possesses a distinct essence that sets them apart, even in the case of identical twins. In language acquisition, learners’ personality type has emerged as one of the most determining constructions for students’ learning strategy. Through a phenomenological case study, intricate interplay between personality types and language learning strategies of two Indonesian identical twin girls studying English language education were investigated, supported by one triangulator participant. By employing the Oxford (1990) Strategy Inventory for Language Learning and the MBTI test, the researchers gathered the extensive data on their language learning strategy distinctions and personality differences. The results indicate that despite sharing the same upbringing, their diverse personalities - one an ENFJ and the other an ENTJ - have contributed to vastly different cognitive, memorization, compensation, metacognitive, social learning, and affective learning approaches. The findings provide intriguing insights into the intricacies of language acquisition and highlight the significance of individual differences in shaping the learning styles.